Representation of Hedonism Lifestyle in Advertising (Semiotics Analysis on Zalora Ads Free Version 30 Days Returns) - Firdaus, Firdaus; Ronda, Mirza; Napitupulu, Frengki (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to understand the Representation of the Hedonism lifestyle in Zalora's 30 Day Returns Free Version of Advertising. In this study, the researcher used a qualitative descriptive type of research. Qualitative description (QD) is a word used for qualitative research used in a descriptive study. This type of qualitative descriptive research is usually used in research on social phenomena. While the method of analysis, the researcher uses the semiotic analysis model of Charles Sanders Pierce. Peirce's theory of semiotics is the science or technique (method) of analysis that explains the sign system. A sign is something that is visible, leads to something, can represent the relationship between the sign and the recipient of the sign that is representative and refers to the interpretive. Peirce separates the sign system (semiotics) into 3 elements that have been included in his triangle theory, namely the sign (sign), the sign reference (object), and the use of the sign (interpretant). While the results and discussion in this study concluded that: the free version of the 30-day return zalora advertisement is not only about promoting fashion items, but also the meaning of the hedonistic lifestyle that is inserted through the scenes. The meaning of the hedonistic lifestyle is seen when the woman puts the measure of her pleasure in life on materialist goods. When he does not have luxurious and stylish clothes, he will feel sad and worried. Conversely, when he has an abundance of luxury goods, he will feel happy and get pleasure in himself (hedonism). In addition to the enjoyment of women's lives as measured by materialist objects as above, the purchase of fashion items in very large and excessive quantities is also the meaning of the hedonistic lifestyle that is inserted in this 30-day return free version of the Zalora advertisement. Various types of fashion as a result of unreasonable purchases are scattered in the room without using them.